2020
DOI: 10.1038/s41746-020-0224-8
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of retention in remote digital health studies: a cross-study evaluation of 100,000 participants

Abstract: Digital technologies such as smartphones are transforming the way scientists conduct biomedical research using real-world data. Several remotely-conducted studies have recruited thousands of participants over a span of a few months. Unfortunately, these studies are hampered by substantial participant attrition, calling into question the representativeness of the collected data including generalizability of findings from these studies. We report the challenges in retention and recruitment in eight remote digita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

34
264
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 299 publications
(331 citation statements)
references
References 77 publications
(79 reference statements)
34
264
7
Order By: Relevance
“…However, it is equally critical to develop and continuously improve on an engaging digital platform that provides value to participants and researchers. This has proven to be extremely challenging, with a recent analysis of eight different digital research programs involving 100,000 participants having a median duration of retention of only 5.5 days 29 . Digital trials such as DETECT also do come with unique challenges to assure privacy and security, which can only be dealt with by effectively informing participants before consent, storing the data with the appropriate level of security and providing access to the data only for research purposes 30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it is equally critical to develop and continuously improve on an engaging digital platform that provides value to participants and researchers. This has proven to be extremely challenging, with a recent analysis of eight different digital research programs involving 100,000 participants having a median duration of retention of only 5.5 days 29 . Digital trials such as DETECT also do come with unique challenges to assure privacy and security, which can only be dealt with by effectively informing participants before consent, storing the data with the appropriate level of security and providing access to the data only for research purposes 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent software platforms like Research-Kit 14 and ResearchStack 15 facilitate the use of mobile technology to recruit and consent patients into studies 16 . The first wave of app-based studies have shown that patients can provide valuable information, with the appropriate recruitment and retention strategies 17 , to advance our understanding of disorders over time, generating new insights about diseases 18,19 and overall health 20,21 . This work contributes to the emerging area of research on digital phenotyping from patient-generated health data, specifically from data collected through smartphone applications 13,22 . Digital phenotyping aims at the automatic characterization of a patient's phenotype using electronic data.…”
Section: Introductionmentioning
confidence: 99%
“…The present study also surfaces challenges in the use of wearable technology for longitudinal monitoring. Recent research has shown that participant retention ( 56 ) and compliance ( 57 ), i.e., the amount of time the wearable sensor patch is worn continuously, remains a challenge. Of the 112 enrolled participants, only 22 (19.6%) wore the patch for at least 24 h across all three sessions.…”
Section: Discussionmentioning
confidence: 99%